Principles of organizational behavior The handbook of evidence-based management - Pearce, Craig L.; Locke, Edwin A. (Hoboken, New Jersey Wiley, 2023)
Explore invaluable management advice informed by the latest in organizational and industrial behaviour research

In the newly revised Third Edition of Handbook of Principles of Organizational Behavior: Indispensable Knowledge for Evidence-Based Management, world-renowned organizational behaviourists Edwin A. Locke and Craig L. Pearce deliver a comprehensive and authoritative discussion of sound management practices informed by the most recent evidence and research in organizational and industrial psychology.

In the book, the authors present:

Complimentary and downloadable video material linked to each chapter
Executive interviews and author interviews, new cases, assessments, inventories and exercises
Updated chapters written by world-leading experts on the covered topics
An indispensable resource for students of human resources, organizational behaviour, industrial psychology, public administration and related subject...
Preface ix

Acknowledgements xiii

Introduction xv

1 Select on Intelligence 1
Frank L. Schmidt and In-Sue Oh

2 Select on Conscientiousness and Emotional Stability 27
Michael K. Mount and Murray R. Barrick

3 Structure Interviews to Recruit and Hire the Best People 47
Cynthia Kay Stevens

4 Attain Emotional Control by Understanding What Emotions Are 65
Edwin A. Locke

5 Motivate Employee Performance Through Goal Setting 83
Gary P. Latham

6 Cultivate Self-Efficacy for Personal and Organizational Effectiveness 113
Albert Bandura

7 Pay for Performance 137
Kathryn M. Bartol

8 Promote Job Satisfaction Through Mental Challenge 161
Timothy A. Judge, Ryan Klinger, and Meng Li

9 Follow the Science to Make Training Work 179
Eduardo Salas and Kevin C. Stagl

10 Embed Performance Appraisals into Broader Performance or Management Systems 211
Maria Rotundo and Kelly D. Murumets

11 Use Participation to Share Information and Distribute Knowledge 237
John A. Wagner III

12 Recognizing Employees 255
Jean M. Phillips, Kathryn E. Dlugos, and Hee Man Park

13 Sustain Organizational Performance Through Continuous Learning, Change, and Realignment 271
Michael Beer

14 Empowerment's Pivotal Role in Enhancing Effective Self- and Shared Leadership 293
Jay A. Conger and Craig L. Pearce

15 Effective Use of Power and Influence Tactics in Organizations 311
Gary Yukl

16 Engage in Visionary Leadership 329
David A. Waldman

17 Foster Trust Through Ability, Benevolence, and Integrity 345
Jason A. Colquitt and Michael D. Baer

18 Teamwork in Organizations: The Best Teams Learn, Adapt, and Are Resilient 365
Allison M. Traylor, Scott Tannenbaum, Eric J. Thomas, and Eduardo Salas

19 Compose Teams to Ensure Successful External Activity 387
Deborah Ancona, Henrik Bresman, and David Caldwell

20 Manage Intrateam Conflict Through Collaboration 403
Laurie R. Weingart, Karen A. Jehn, and Kori L. Krueger

21 Clarity, Conciseness, and Consistency Are the Keys to Effective Communication 429
Jean Phillips, Kameron M. Carter, and Dorothea Roumpi

22 Stimulate Creativity by Fueling Passion 443
Colin M. Fisher and Teresa M. Amabile

23 Manage Stress at Work Through Preventive and Proactive Coping 463
Ralf Schwarzer and Tabea Reuter

24 Conflict Resolution Through negotiation and Mediation 483
Kevin Tasa and Ena Chadha

25 Achieve Entrepreneurial Growth Through Swiftness and Experimentation 503
Jaume Villanueva, Harry J. Sapienza, and J. Robert Baum

26 Achieve Work-Family Balance Through Individual and Organizational Strategies 531
Malissa A. Clark, Katelyn N. Sanders, and Boris B. Baltes

27 Use Advanced Information Technology to Transform Organizations 551
Dongyeob Kim, Maryam Alavi, and Youngjin Yoo, Ph.D.

28 Make Management Practice Fit national Cultures and the Global Culture 575
Miriam Erez

29 Strategy and Structure for Effectiveness 595
John Joseph and Metin Sengul

Index 621
Previously published under the title: Handbook of principles of organizational behavior.
Includes bibliographical references and index.
Keywords: Organizational behavior